The effects of different short-term Storage Modalities on the Antioxidant Capacity of Beetroot Juice: Short term refrigeration of Beetroot Juice Better Preserves its Antioxidant Capacity - Munguti , Jeremiah; Ndegwa Makanyab, Andrew; Obimbo Madadi, Moses; Kipkorir , Vincent (Algerian Journal of Biosciences, 2023)
Beetroot contains phytochemicals that have anti-inflammatory and antioxidant properties. The nutritional quality of consumed beetroot is, however, affected by post-harvest processing. To determine the effect of different short-term storage modalities on beetroot antioxidant activity. Beetroot samples were freshly sourced and randomly divided into 3 groups: Group A was used to prepare fresh beetroot juice on the day of analysis; Group B was used to prepare beetroot juice that was then refrigerated for one week before analysis while Group C was kept whole at room temperature for one week and then used to prepare the beetroot juice. Beetroot juice was prepared by mixing one-part of beetroot with one-part of clean water and blending the mixture. It was then freeze-dried, and the resultant powder used to measure the residual antioxidant activity and for phytochemical analysis to determine the presence of flavonoids. At analysis, all the three samples contained the same biochemical compounds and had no notable gross differences in smell, viscosity, and consistency. The juice prepared from beets stored whole for a week was of a more intense colour compared to that of the refrigerated beetroot juice. At lower concentrations of the extracts, refrigerated juice had lower antioxidant activity while that stored as a whole had the highest. Refrigerated juice had the highest antioxidant activity (IC50 of 10,457.11 mg/ml) while beetroot stored had the lowest activity (IC50 of 210,069.4 g/ml). Short term refrigeration of beetroot juice better preserves its antioxidant capacity.